2020
DOI: 10.3389/fonc.2020.01232
|View full text |Cite
|
Sign up to set email alerts
|

Gene Co-expression Is Distance-Dependent in Breast Cancer

Abstract: Breast carcinomas are characterized by anomalous gene regulatory programs. As is well-known, gene expression programs are able to shape phenotypes. Hence, the understanding of gene co-expression may shed light on the underlying mechanisms behind the transcriptional regulatory programs affecting tumor development and evolution. For instance, in breast cancer, there is a clear loss of inter-chromosomal (trans-) co-expression, compared with healthy tissue. At the same time cis-(intra-chromosomal) interactions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 70 publications
9
43
1
Order By: Relevance
“…By observing the discrepancy between the cis-rate of ccRC progression stages with those observed in breast cancer molecular subtypes (García-Cortés et al, 2020), regarding that high proportion of intra-chromosome interactions are observed in those phenotypes with a worst prognosis we may argue the following:…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…By observing the discrepancy between the cis-rate of ccRC progression stages with those observed in breast cancer molecular subtypes (García-Cortés et al, 2020), regarding that high proportion of intra-chromosome interactions are observed in those phenotypes with a worst prognosis we may argue the following:…”
Section: Discussionmentioning
confidence: 98%
“…(1) pre-normalization quality control, (2) batch and bias corrections (normalization) and (3) post-normalization quality control. Data pre-processing was conducted as previously (Drago-García et al, 2017;Espinal-Enriquez et al, 2017;de Anda-Jáuregui et al, 2019b,c;García-Cortés et al, 2020;Serrano-Carbajal et al, 2020). Briefly, we assessed (a) biotype abundances, to assure that samples contained protein coding genes.…”
Section: Data Pre Processingmentioning
confidence: 99%
See 3 more Smart Citations